PENGARUH PROFITABILITAS, LIKUIDITAS DAN ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BEI 2018- 2022 - Rahma Zainatul Hasnah; Era Sonita (Jurnal Ekonomi dan Bisnis, 2025)
This study was motivated to find out how the effect of prooofitability as measured by Retun On Asset, liquidity as measured by Cuurent Ratio ang cash flow on stock prices in telecomunications companies listed on the IDX 2018-2022. This study uses a decriptive quantitative approach. The sample was selected using purposive sampling method so that a sample of 11 companies was obtained from a total of 21 telecommunications company populations. Data collection using the documentation method with secondary data in the form of company financial reports for 2018-2022. Data analysis techniques using descriptive statistical tests, classical assumpion tests consisting of normality tests, multicollinearity tests, autocorrelation tests, detetmination coefficient test and hypothesis tests. Partial research reults show that profitability and liquidity have no significant effect on stock prices, cash folw has a significant effect on stock prices. Simultaneously profitability, liquidity and cash folw have no effect on stock prices, based on the coefficient of determination test shows that profitability, liquidity and cash flow affect stock prices by 12,8%, while 87,2% is influenced by other variables.